S97 Is an Increased Tendency to Clot a Risk Factor For Developing Idiopathic Pulmonary Fibrosis?. (19th November 2012) - Navaratnam, V; Fogarty, A; McKeever, T; Thompson, N; Jenkins, RG; Johnson, SR; Dolan, G; Kumaran, M; Pointon, K; Hubbard, RB
Abstract : Background: The aetiology of idiopathic pulmonary fibrosis (IPF) remains poorly understood. Recent animal studies and epidemiological data have suggested that activation of the coagulation cascade in the lung may have an important role in the pathogenesis of IPF. Methods: We recruited incident cases of physician diagnosed IPF from five teaching hospitals and eight district general hospitals in England and Wales. Age and sex matched general population controls were recruited from the same region. Participants were asked for details of lifetime occupational history, current or previous illnesses, medication and smoking. Each case and control then had a venous blood sample taken for a thrombophilia screen, including inherited and acquired clotting defects. We also collected high resolution computed tomography (HRCT) scans for all cases, which were reviewed by two experienced thoracic radiologists to confirm the diagnosis of IPF. After excluding individuals on warfarin, logistic regression was used to estimate odds ratios for the association between a prothrombotic state and IPF, adjusting for age, sex and highly sensitive C Reactive Protein (hsCRP). Individuals were defined as being prothrombotic if they had at least one clotting defect present. The analysis was then repeated, stratifying cases by radiological diagnosis. Results: Our study included 306 incident cases of IPF(mean age at diagnosis 72.6 years, 70.6% male) and 256 controls (see Table 1 ). We found an increased tendency to clot among our cases (Odds Ratio [OR] 4.67; 95% Confidence Interval [CI] 3.00 to 7.23) compared to controls. After stratifying by radiological diagnosis, this association was stronger in those with definite usual interstitial pneumonia (UIP) (OR 5.86; 95% CI 3.08 to 11.15) compared to probable UIP (OR 3.47; 95% CI: 1.92 to 6.29). There was no effect modification by age, sex or hsCRP. Conclusion: An increased tendency to clot appears to be an independent risk factor for developing IPF. A clinical trial using one of the new, safer anticoagulants may be warranted.